INFRASTRUCTURE SUPPORT FOR THE DEVELOPMENT OF REGIONAL ECONOMIC SYSTEMS - R. Safiullin, Marat; R. Kadyrov, Azat; M. Galeeva, Gulnaz (Gênero & Direito, 2020)
This article considers the problems of infrastructure financing, which is necessary for the successful development of regional economic systems. To identify the current problems in the development of investment attractiveness of the Russian regions, we selected the following factors: availability and level of provision of industrial, social, transport, and other infrastructure with facilities, government expenses on the creation and development of regional infrastructure. The study consists of several stages and is based on data published on the official websites of the World Bank, Gazprombank, the Ministry of Economic Development of the Russian Federation, and the Ministry of Regional Development of the Russian Federation. The study shows that the absolute leaders in terms of infrastructure investments are such countries as China, the United States, and India. In the total amount of infrastructure investments, transport infrastructure and telecommunications have an absolute advantage. In recent years, one of the development priorities of the Russian regions has been investing in physical culture and sports infrastructure facilities. This is due to major international sporting events and increasing the investment attractiveness of the regions. An important trend in the development of infrastructural support for the development of regional economic systems has been the conclusion of international investment transactions (IIT) and regional agreements. Most countries and regions, leading in the inflow of foreign direct investment, are the leaders in terms of infrastructure development at the same time.